Prolonged operative time predicts postoperative deep venous thrombosis in head and neck cancer patients who undergo free flap reconstruction - Kevin C. Lee; Nicholas A. Waring; Victoria X. Yu; Ogoegbunam Okolo; Salvatore M. Caruana; Scott H. Troob; Anuraag S. Parikh (Laryngoscope Investigative Otolaryngology, 2023)
Abstract Objective This study sought to quantify the deep venous thrombosis (DVT) incidence in head and neck cancer (HNC) patients undergoing free tissue transfer and to identify independent predictors of postoperative DVT. Materials and Methods This is a cross‐sectional study of the National Surgical Quality Improvement Program database from 2010 through 2020. The sample included all HNC surgical patients treated with free flap reconstruction. The study outcome was the presence of a DVT requiring treatment within 30 days of surgery. Univariate analyses were performed using chi‐squared and independent t‐tests. A multiple logistic regression model was created using all significant univariate predictors. Results A total of 3954 patients were identified, of whom 53 (1.3%) experienced a postoperative DVT. The only medical comorbidity associated with DVT was COPD (RR = 2.7 [1.3, 5.4]; p < .01). Operative time longer than 9 hours (RR = 1.9 [1.0, 3.2]; p = .04) and length of stay longer than 10 days (RR = 1.9 [1.1, 3.2]; p = .02) were associated with greater DVT rates. In the multivariate analysis, only COPD (p < .01) and operative time (p = .02) were independently associated with DVT risk. The presence of a DVT was found to increase the relative risk of readmission (RR = 2.1 [1.2, 3.6]; p < .01) and non‐home disposition (RR = 2.4 [1.7, 3.5]; p < .01). Conclusions The incidence of DVT in HNC free flap patients was comparable to what has been reported in the general population of HNC surgery patients. Operative time >9 h and COPD history were independent risk factors for DVT in this subset of patients. Symptomatic DVTs necessitating treatment were accompanied by poorer post‐hospitalization outcomes. Level of Evidence Level 3.